Aggregation Behavior of Poly(Acrylic acid‐co‐Octadecyl Methacrylate) and Bovine Serum Albumin in Aqueous Solutions. Issue 3 (25th February 2021) - Zhou, Mengmeng; Bi, Yutong; Zhou, Haijun; Chen, Xiaoqi; Zhang, Fen; Li, Yantao; Qu, Xiongwei
Abstract: Polymer‐protein complexing systems have been extensively studied because of their wide application in biomedicine and industry. Here, we studied the aggregation behavior of the hydrophobically associating water‐soluble polymer poly(acrylic acid‐co‐octadecyl methacrylate) [P(AA‐co‐OMA)] prepared with nonionic surfactant as an emulsifier and bovine serum albumin (BSA) in aqueous solution. We identified the optimal composite conditions of P(AA‐co‐OMA) and BSA aqueous solution. We measured the zeta potential, dynamic light‐scattering particle size, and surface tension of P(AA‐co‐OMA) and BSA mixed aqueous solution. The results showed that the aggregation behavior between the polymer and BSA relied mainly on the hydrophobic interactions between the molecules. In addition, the best compounding condition was 8 wt.% of P(AA‐co‐OMA) content. The structure of hydrophobically associating polymer P(AA‐co‐OMA) and its aggregation with BSA were characterized by Fourier‐transform infrared spectroscopy. The infrared spectroscopy results identified the hydrogen bonding behavior of the amino and carboxyl groups between the polymer and BSA. This behavior was also confirmed using thermogravimetric analysis and differential scanning calorimetry. The thermal decomposition temperature and melting temperature of BSA changed before and after it was combined with the polymer. We measured the morphology of the polymer BSA aggregate with 8 % polymer content by transmission electron microscopy. The binding mechanism was investigated, as well. Abstract : The aggregation behavior between P(AA‐co‐OMA) and BSA, which primarily depends on hydrophobic aggregation and hydrogen‐bonding interaction, has been investigated. As shown in the figure, the gray area reveals that the hydrophobic regions of P(AA‐co‐OMA) and BSA gather together, and the hydrophilic areas are located next to each other as a result of the hydrogen‐bonding interaction.